Applying the perceived probability of risk and bias toward optimism: Implications for travel decisions in the face of natural disasters. (June 2018) - Rittichainuwat, Bongkosh; Nelson, Robert; Rahmafitria, Fitri
Abstract: Unperceived risk leads to lack of preparedness. This study aims to examine tourists' risk perception and travel decisions using as variables demographics, knowledge about safety, and country of residence. Samples were gathered in Thailand, Japan, Australia, and Indonesia. A total of 916 completed questionnaires of five replicated surveys were used in this study. More than halve of the respondents whose country had been affected by the Indian Ocean tsunami in 2004 did not perceive tsunami risk when 10 years has passed. Frequency of tsunami occurrence was positively related to perceived tsunami probability. This study confirms the theory of probability that low frequency of a natural disaster results in unperceived risks. Even if their destination had a history of tsunamis, tourists' perceived risk of another such occurrence happening during their visit is low (that is, the risk of natural disaster is low). While the literature in earth science found that residents of risky areas tend to be optimistic about the place where they live, our study extends the theory of optimistic bias to indicate that the same optimistic bias is applicable to tourists. Asia and Southeast Asia were perceived as tsunami-prone but tourists still travelled there. Our study found that tourist risk perception was related to frequency of tsunami occurrence and was destination specific. The perception of probability of a natural disaster is also related to proximity and past experience. Replications are necessary to validate results before generalization. Highlights: Optimistic bias related to tsunami frequency and proximity to risk sources. Most tourists were optimistic about the place where they travel. Low frequency of tsunami occurrence created unperceived risks at tsunami-prone destinations. Tourists with more knowledge about tsunami safety perceived less risk. Perceived tsunami probability is destination specific.